THE CHOICE OF THE PROFESSIONAL QUALIFICATION IN PHYSICAL EDUCATION: THE INFLUENCE OF THE CORPORAL IMAGE. (Fiep Bulletin - online, 2011)
The changes happened in the formation of the professionals of the Physical Education as consequence of social, legal, cultural and educational transformations, at the same time where they had promoted ruptures in the traditional model of academic formation of the professors of Physical Education, opening spaces for the courses of graduation with new specializations, had also conserved some standards of the incorporated previous resumes historically for the profession. The present article prioritized in its analyses concerning the professional qualification in Physical Education, the influence of the corporal image, pointing the contradictions that take the professional futures to the adoption of the criterion of the self-image associated with the professional option, forgetting those criteria that effectively are responsible for the formation of a good professional of Physical Education.
Keywords: physical education; professional formation; corporal image